2014
DOI: 10.4172/2167-0889.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of AgNOR Proliferative Index in gallbladder carcinoma - A potential alternative to frozen section analysis

Abstract: The aim of the present study is to calculate the AgNOR proliferative index in benign and malignant lesions of the gallbladder and to study their relationship with different clincopathological parameters. It also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
2
Order By: Relevance
“…In the present study, AgNOR counts observed in chronic cholecystitis (2.44±0.31) were higher in comparison to Gupta et al and Gupta et al (1.89±0.96 and 2.08±0.37 and Misra et al (1.970.28). 2,8,9 In cases of hyperplasia, the average AgNOR count in the present study was lower than that found in studies by Gupta et al and Misra et al 7,8 However the mean AgNOR counts in carcinoma were higher in our study than that observed by Gupta et al and Misra et al but much less than those of Gupta et al though they had counted AgNORs separately in different grades of carcinoma. 2,7,8 Suzuki et al had found that mean AgNOR scores in carcinoma were low in comparison to other studies (3.28±1.38).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In the present study, AgNOR counts observed in chronic cholecystitis (2.44±0.31) were higher in comparison to Gupta et al and Gupta et al (1.89±0.96 and 2.08±0.37 and Misra et al (1.970.28). 2,8,9 In cases of hyperplasia, the average AgNOR count in the present study was lower than that found in studies by Gupta et al and Misra et al 7,8 However the mean AgNOR counts in carcinoma were higher in our study than that observed by Gupta et al and Misra et al but much less than those of Gupta et al though they had counted AgNORs separately in different grades of carcinoma. 2,7,8 Suzuki et al had found that mean AgNOR scores in carcinoma were low in comparison to other studies (3.28±1.38).…”
Section: Discussioncontrasting
confidence: 75%
“…2,8,9 In cases of hyperplasia, the average AgNOR count in the present study was lower than that found in studies by Gupta et al and Misra et al 7,8 However the mean AgNOR counts in carcinoma were higher in our study than that observed by Gupta et al and Misra et al but much less than those of Gupta et al though they had counted AgNORs separately in different grades of carcinoma. 2,7,8 Suzuki et al had found that mean AgNOR scores in carcinoma were low in comparison to other studies (3.28±1.38). 10 The increase in AgNOR counts from chronic cholecystitis to hyperplasia and hyperplasia to carcinoma were found to be statistically significant (p<0.05).…”
Section: Discussioncontrasting
confidence: 75%